Kingdom - Brenan, Craig (My University, 2014)
Performed by: Craig Brenan, trombone; John Ellis, tenor saxophone, bass clarinet; Connor Learmonth, bass clarinet, clarinet; Raymond Baril, alto saxophone, bass clarinet, clarinet; Adrienne Lorway, clarinet, bass clarinet; Dave Morgan, trumpet, flugelhorn; Ted Poor, drums. Conducted by Allan Gilliland. Composition by Craig Brenan. Arranging assistance from Florian Ross. Recorded February 2014 by Stew Kirkwood at Sound Extractor Studio. Mixed by Jim Brenan, Spencer Cheyne, Craig Brenan. Mastered by Florian Ross. Produced by Craig Brenan.
Rocket sauce (3:18 min.) -- Dream #7 (5:51 min.) -- The uninvited (5:20 min.) -- Woodward (3:50 min.) -- Furious (1:47 min.) -- Dogleg (6:53 min.) -- Kingdom (6:03 min.) -- Were the colour (6:19 min.) -- The sounds around the house (6:28 min.).
Keywords: trombone music; jazz